Effects of Simvastatin on the Metabolism of Vonoprazan in Rats Both in vitro and in vivo - Hong, Yun; Dai, Da-Peng; Cai, Jian-Ping; Wang, Shuang-Hu; Wang, Yi-Ran; Zhao, Fang-Ling; Zhou, Shan; Zhou, Quan; Geng, Pei-Wu; Zhou, Yun-Fang; Xu, Xue; Shi, Ji-Hua; et al. (Drug Design, Development and Therapy, 2022)
To study the potential drug-drug interactions between simvastatin and vonoprazan and to provide the scientific basis for rational use of them in clinical practice. An incubation system was established with rat liver microsomes, and the main metabolite of vonoprazan M-I was detected by UPLC-MS/MS. The IC value of simvastatin was then calculated and its inhibitory mechanism against vonoprazan was also analyzed. Twelve SD rats were randomly divided into 2 groups, then they were given simvastatin or saline for 2 weeks continuously. On the day of the experiment, both groups were intragastrically administered with vonoprazan once, followed by the collection of blood at different time points. Then the plasma concentration of vonoprazan and M-I in rats were detected by UPLC-MS/MS. In vitro experiments revealed that simvastatin could inhibit the metabolism of vonoprazan, and its inhibition type belonged to the mixed non-competitive and competitive inhibition model. In vivo experiments in rats demonstrated that the area under concentration time curve (AUC) of vonoprazan was decreased but the clearance (CLz/F) of it was increased in the simvastatin administrated group, as compared to those of the control group. However, M-I in simvastatin treated group exhibited the higher AUC and lower CLz/F values compared to those in the control group. These data indicated that multiple doses of simvastatin administration could reduce the plasma concentration of vonoprazan and accelerate its metabolic rate in rats. Simvastatin could inhibit the metabolism of vonoprazan in vitro but multiple doses of simvastatin exhibited the opposite effect In vivo. Altogether, our data indicated that an interaction existed between simvastatin and vonoprazan and additional cares might be taken when they were co-administrated in clinic.